THE PROCESS OF IMPLEMENTING NEUROFINANCE IN STATE ORGANIZATIONS - Abdukhalimova Madina Khasanboy qizi (Modern American Journals, 2025)
This work examines the emerging field of neurofinance and explores how it can be systematically implemented within state organizations to improve financial decision-making and public policy. Building on insights from traditional finance, behavioral finance, and neuroeconomics, the study emphasizes that financial decisions are shaped not only by rational analysis but also by neural activity, emotional states, hormonal processes, and inherited traits. The text integrates findings from neuroscience—such as fMRI, EEG, hormonal profiling, and physiological markers—to explain how risk perception, reward anticipation, and market behavior are rooted in brain mechanisms.
Keywords: Fintech, neuroimaging techniques, Electroencephalography (EEG), Functional Magnetic Resonance Imaging (fMRI), dopamine and serotonin, hormonal profiling, fiscal governance, skin conductance response (SCR), heart rate variability (HRV)